The Effect of Concrete Topping Thickness on the Vibration Response of Prestressed and Precast Hollow Core Flooring Systems - Rahimi, Mohammad Imran; Abd Ghafar, Nor Hayati; Ibrahim, Zainah; Mohd Jaini, Zainorizuan; Abd Aziz, Nor Azmina Zafira; Mat Gamadi, Nur Emilia (International Journal of Integrated Engineering, 2020)
In the field of floor vibration, there is a need to consider several vibration parameters. Mass, stiffness, damping and frequency are the most common causes of excessive vibration to floor systems. However, there is a need for better understanding of vibration caused by the interaction between stiffness and added mass by concrete topping. This paper presents a vibration behaviour analysis on the effects of concrete topping on prestressed and precast hollow core floor (PPHCF) systems. Experimental modal analysis (EMA) was performed on a selected floor area in a four-storey office building by conducting an ambient test. From the EMA, the results were further verified using finite element analysis (FEA). During the FEA, numerical dynamic analysis was conducted with the implementation of the finite element model by increasing the topping thickness. For thickness ranging between 0mm to 350mm with an interval of 25mm, the optimum value of concrete topping thickness was 150mm. From the analysis, the behaviour of the floor systems with concrete toppings measuring lower than 150mm thick was found to be dominated by mass whereas for concrete toppings measuring more than 150mm thick, the behaviour of the floor system was found to be dominated by stiffness.